Association Between Lactate-to-Albumin Ratio and 28-Day All-Cause Mortality in Critical Care Patients with COPD: Can Both Arterial and Peripheral Venous Lactate Serve as Predictors? - Zhao K; Zhou L; Ni Y; Tao J; Yu Z; Li X; Wang L (International Journal of COPD)
Kelan Zhao,1,* Linshui Zhou,1,* Yeling Ni,1 Jieying Tao,1 Ziyu Yu,1 Xiaojuan Li,2 Lu Wang1 1Department of Pulmonary and Critical Care Medicine, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, People’s Republic of China; 2Department of Scientific Research, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaojuan Li, Department of Scientific Research, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, People’s Republic of China, Email 20093002@zcmu.edu.com Lu Wang, Department of Pulmonary and Critical Care Medicine, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, People’s Republic of China, Email lulumm8809@163.comBackground: Lactate-to-albumin ratio (LAR) has been reported as a useful predictor for multiple critical illnesses. However, the association between LAR and mortality in patients with chronic obstructive pulmonary disease (COPD) remains unclear. This study aims to clarify the correlation between LAR and 28-day all-cause mortality in patients with COPD and to investigate whether LAR calculated using arterial lactate (AL) or peripheral venous lactate (PVL) can serve as predictive indicators.Methods: A total of 1428 patients from the Medical Information Mart for Intensive Care (MIMIC) IV database (version 2.2) and 2467 patients from the eICU Collaborative Research Database (eICU-CRD, version 2.0) were included in this study. Propensity score matching (PSM) method was conducted to control confounders. Cox proportional hazards model, Kaplan–Meier survival method, subgroup analysis and receiver operating characteristic (ROC) analysis were performed to assess the predictive ability of LAR. To verify our hypothesis, data from the two databases were analyzed individually.Results: After adjusting for covariates, LAR calculated using either AL (MIMIC IV, HR = 1.254, 95% CI, 1.013– 1.552, P = 0.038) or PVL (eICU-CRD, HR = 1.442, 95% CI, 1.272– 1.634, P < 0.001) was independently associated with 28-day all-cause mortality in COPD patients. Kaplan–Meier analysis showed that patients with higher LAR value had significantly higher all-cause mortality (all P < 0.05). This association was consistent across subgroup analyses. In addition, the ROC analysis suggested that LAR calculated using PVL may have better predictive performance compared to using AL.Conclusion: LAR calculated using both AL and PVL can independently predict the 28-day all-cause mortality after ICU admission in patients with COPD and higher level of LAR is related to higher mortality risk.Keywords: chronic obstructive pulmonary disease, lactate-to-albumin ratio, all-cause mortality, 28-day, prognosis factors, cohort